Economic impact assessment of Cowdria ruminantium infection and its control in Southern Africa - Minjauw, B.; Kruska, Russell L.; Odero, A.; Randolph, Thomas F.; McDermott, John J.; Mahan, S.M.; Perry, Brian D. (International Society for Veterinary Epidemiology and Economics, 2000)
Heartwater is a tick-borne disease of cattle, sheep and goats and some wild ruminants prevalent in much of Africa and the Caribbean. It is caused by the rickettsial organism Cowdria ruminantium and transmitted by ticks of the genus Amblyomma. The disease has traditionally been controlled by the use of chemical acaricides to prevent and control infection transmission. A blood-based vaccine for heartwater exists, containing live Cowdria organisms, but it has not been widely adopted as it requires a strict cold chain and can result in severe clinical reactions! Current research focuses on the Development of safer and more effective inactivated vaccines. This study examines the economic impact of heartwater in the countries of the Southern African Development Community (SADC) region, and of the new vaccines under Development to control the disease.